Large deviations for stochastic predator–prey model with Lévy noise - Sridevi, C.S.; Suvinthra, Murugan; Balachandran, Krishnan (Nonlinear Analysis: Modelling and Control, 2024)
This paper discusses the large deviations for stochastic predator–prey model driven by multiplicative Lévy noise. Using Galerkin approximation, we initially prove the existence and uniqueness of solution. Due to the equivalence between Laplace principle and large deviation principle under a Polish space, the method of weak convergence has been followed in order to establish our results for this coupled system of equations.